Pembelajaran Bahasa Indonesia di Sekoah Dasar - Suparlan Suparlan (FONDATIA, 2020)
Indonesian language lessons in elementary schools are basically teaching children to communicate using Indonesian. Indonesian language lessons in elementary schools that are directed at improving students' ability to communicate in Indonesian both spoken and written. Elementary schools have the goal of creating or preparing students to have the ability to continue to a higher level of education. One of the efforts made to achieve this goal is to improve student achievement.